2004
DOI: 10.1111/j.1365-2206.2004.00309.x
|View full text |Cite
|
Sign up to set email alerts
|

Breakdown of teenage placements in Swedish foster and residential care

Abstract: A B S T R AC TThis article deals with the problem of breakdown in different types of out-of-home care (foster care/residential care) for Swedish teenagers. How often are such placements prematurely terminated against the wishes and intentions of child welfare authorities? Which factors appear to increase or decrease the risk of placement breakdown? The sample consists of a national cohort of 776 youths who started 922 placements during 1991. Every placement was followed in municipal case files for a maximum pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
111
2
10

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(130 citation statements)
references
References 26 publications
5
111
2
10
Order By: Relevance
“…There also is evidence that children placed in residential settings change placements less frequently than children in nonrelative family foster homes (Sallnäs et al 2004). Most studies of placement stability exclude children who are placed in shelter settings or who remain in care for limited periods.…”
Section: Nih Public Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…There also is evidence that children placed in residential settings change placements less frequently than children in nonrelative family foster homes (Sallnäs et al 2004). Most studies of placement stability exclude children who are placed in shelter settings or who remain in care for limited periods.…”
Section: Nih Public Accessmentioning
confidence: 99%
“…Several studies report that relative and kinship foster care placements are more stable than other types of out-of-home placements (Fernandez 1999;Webster et al 2000;Sallnäs et al 2004). There also is evidence that children placed in residential settings change placements less frequently than children in nonrelative family foster homes (Sallnäs et al 2004).…”
mentioning
confidence: 99%
“…This rate varies a great deal at the international level, because it is estimated that between 20 to 50% of placements ends this way (Berry & Barth 1990;Fratter, Rowe, Sapsford, & Thoburn, 1991;Millham, Bullock, Hosie, & Haak, 1986;Minty, 1999;Sallnäs, Vinnerljung, & Westermark, 2004;Stone & Stone, 1983).…”
Section: Rates Of Breakdown and Its Consequencesmentioning
confidence: 99%
“…have undergone the most placement changes (James, Landsverk, & Slymen, 2004;Palmer, 1996). Children who undergo a larger number of changes will also be more likely to obtain worse academic results and to suffer from other problems at school (Biehal, Clayden, Stein, & Wade, 1995;Eckenrode, Rowe, Laird, & Brathwaite, 1995;Sallnäs et al, 2004). Foster breakdown has also been linked to increased difficulties for these children after their transition to an independent life, including antisocial behavior, chronic unemployment, delinquency, psychoactive substance consumption, or difficulties in their personal relations, among other problems (Fanshel et al, 1990;Festinger, 1983;Mech, Ludy-Dobson, & Hulseman, 1994).…”
Section: Rates Of Breakdown and Its Consequencesmentioning
confidence: 99%
“…There are various types of professions operating in the field, nearly half of the employees have no formal education and the methods practiced differ considerably (IVO 2013). Swedish residential care is not evaluated to any large extent, but studies have revealed a high prevalence of disruptions (Sallnäs, Vinnerljung, and Kyhle Westermark 2004), unsatisfactory access to welfare resources (Sallnäs, Wiklund, and Lagerlöf 2012) and poor long-term effects (Sallnäs and Vinnerljung 2008). The Swedish government advocates the application of evidence-based interventions (Bergmark, Bergmark, and Lundström 2011), but the use of specific methods remains unregulated and hence, is not formally monitored by the Inspectorate.…”
Section: Rising Placements Privatisation and De-professionalisationmentioning
confidence: 99%